2022
DOI: 10.21037/apm-22-246
|View full text |Cite
|
Sign up to set email alerts
|

How a very large sarcomatoid lung cancer was efficiently managed with lattice radiation therapy: a case report

Abstract: Background: The management of large tumors represent a concerning issue in the palliative setting.Since a surgical approach is excluded and systemic therapy has reported limited efficacy, the patients are commonly referred for radiation therapy as last resort. However, to improve quality of life and to avoid excessive toxicity, low doses of palliative radiotherapy (RT) are delivered. In these cases, with limited and short response. Lattice radiation therapy (LRT) represents an innovative technique aiming to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Again, a mean tumor regression of around 54% was observed, with no grade ≥3 toxicity. cancer with a T of 19 cm x 16 cm, who received 55 Gy on the hotspots and 20 Gy on the periphery in 5 consecutive fractions, reaching a 70% lesion reduction at 3 months (19). These preliminary data seem to suggest that both LRT approaches could be valid to safely reach a marked T response.…”
Section: Cold Tmementioning
confidence: 75%
See 1 more Smart Citation
“…Again, a mean tumor regression of around 54% was observed, with no grade ≥3 toxicity. cancer with a T of 19 cm x 16 cm, who received 55 Gy on the hotspots and 20 Gy on the periphery in 5 consecutive fractions, reaching a 70% lesion reduction at 3 months (19). These preliminary data seem to suggest that both LRT approaches could be valid to safely reach a marked T response.…”
Section: Cold Tmementioning
confidence: 75%
“…In recent literature, monocentric studies reported positive feedbacks on LRT for large tumor (18,19); however, no trials about LRT safety were conducted until the recent publication of the "LITE SABR M1 trial" (20). This study highlighted the safety of LRT cytoreduction and its promising results en-In addition, it is hypothesized that the gradient generated in the treated volume could improve host immune system response against neoplastic cells both in irradiated and not irradiated sites (abscopal effect) (8).…”
Section: Lattice Radiation Therapy For Large Metastatic Cold Tumorsmentioning
confidence: 99%
“…Emerging data have established RT as a useful therapeutic option also for oligometastatic and oligorecurrent/oligoprogressive disease [16], rare histologies [17,18], or in combination with new drugs available for hormone-sensitive and castration-resistant PC. In recent years, advances in radiation planning and delivery techniques, in particular the advent of new-generation linac with the FFF mode, have improved treatment accuracy and given rise to the adoption of ultrahypofractionated radiation schedules in the form of SBRT [19] in different oncological settings, with acceptable toxicity [20][21][22][23][24][25]. Despite this, local failure after RT still remains a critical issue.…”
Section: Discussionmentioning
confidence: 99%
“…Two approaches to delivering LRT are commonly used. The first approach consists of a sole LRT treatment course with a simultaneous integrated boost, usually delivered in five fractions 5–7 . The second approach combines one to three upfront LRT fractions followed by consolidation radiation therapy with a conventional palliative prescription 8–11 .…”
Section: Introductionmentioning
confidence: 99%